Imperial faith and catholic missions in the grand exhibitions of the Estado Novo - Sánchez-Gómez, Luis Ángel (2009)
During the 1930s Portugal’s Estado Novo developed an impressive array of activities directed at awakening and maintaining Portugal’s “national pride”, in an attempt to define the new regime’s symbolic ideology and consolidate loyalties. Those intentions were reflected in Portugal’s participation in the main international expositions of the time, and in the successful organization of various national expositions, especially those of 1934, 1937, and 1940. The Catholic Church was featured in some form in all of these historical, economic, and colonial events. The purpose of this article is to analyze this participation and consider how it was useful for the Church. Finally, I will show how this participation was turned by the Estado Novo to its own ends.